Analisis Keberhasilan Tiktok Product Ads Terhadap Peningkatan Pendapatan pada Akun Tiktok Shop Pondok Tactical - Asmi Lidya Pradipta Rahayu; Muadz; Septiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
TikTok Ads is one of the promotional tools provided by TikTok Shop or TikTok to increase revenue, in addition to promotional videos and livestreams on TikTok accounts. Shop accounts that use TikTok Ads must carefully consider planning their financing and the best strategy to achieve the desired revenue target. The purpose of this study is to analyze the success of using TikTok Ads as a promotional media to increase revenue on the TikTok Shop Pondok Tactical account. This study uses a quantitative method by collecting revenue data from TikTok Shop Pondok Tactical accounts and conducting an analysis of the success and comparison of the amount of monthly revenue obtained with TikTok Ads and without TikTok Ads. Data analysis was carried out descriptively by analyzing sales data obtained on the TikTok Shop Pondok Tactical account. The results of the study show that TikTok Product Ads has succeeded in increasing revenue at TikTok Shop Pondok Tactical and providing a positive trend towards sales every month. In addition, the time factor and the existing campaign also affect the success of the ads or advertisements that are run. Revenue contribution and Return on Ads Spend must also always be considered so that the company does not suffer losses due to advertising on TikTok Ads